Entre culture in et culture off - Hadrien Dubucs (Territoire en Mouvement)
Artists social and spatial trajectories within a city can be seen as epitomizing change and complexity of the urban contexts in which creative activity takes place. This paper analyses the case of the Japanese artists (about 500) living and working in Paris area, within specific "art worlds" (Becker, 1982) strongly structured by social networks and public or private actors. From ‘off’ artistic spaces in gentrifying and pericentral areas to widely renowned art centers in central districts, the paper enlightens this diversity by analyzing three cases of Japanese artists whose career trajectories are very different : Combination of alternative and mainstream arts, with a frequent mobility between France and Japan ; professional transition from alternative arts organizations to large cultural institutions ; pursuing of a professional project implying residential relocation in rural area. These examples illustrate several aspects of the relationship between activities, places and contributions of art to urban dynamics (cultural supply and urban athmosphere) : borders between ‘in’ and ‘off’ art creation are not clear in artists careers ; they can successively or simultaneously work in many different and complementary urban places ; the urban change and the evolutions of local housing market do not have simple effect on artists trajectories, which depend on many other factors including age, professional opportunities or personal projects.